(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The research explores the role of transformational leadership in enhancing organizational innovation, identifying it as one of the most impactful leadership styles for fostering creativity and improving organizational performance. The study delves into the concept of transformational leadership and its key dimensions, such as inspirational vision, intellectual stimulation, and individualized consideration. It also examines how this leadership style promotes innovation by enhancing social collaboration and influencing organizational culture. Additionally, the research analyzes recent statistics and case studies from companies like Tesla, Apple, and Amazon, highlighting the significant impact of transformational leadership on improving financial and innovative performance in organizations.